KÓRKEM ShÍǴARMADA PSIXOLOGIZMNIŃ FUNKCIYASÍ (A.SULTANOVTÍŃ ShÍǴARMALARÍ MÍSALÍNDA) - Baltabayeva, Nursulu Koshkinbayevna (SCIENCE and SOCIETY, 2026)
The article theoretically and analytically explores artistic psychologism, one of the fundamental characteristics of fiction, and its functions within the poetics of a literary work. The research focuses on the works of the famous Karakalpak writer Alpisbay Sultanov, specifically "Kelinshek bola almaǵan hayal" ("The woman who could not become a bride") and "Baxıtsız shańaraq" ("The unhappy family").